Evaluation of CSR Program Performance through Measuring Community Satisfaction at PT Pertamina Gas Negara, Tbk – Stasiun Kompresor Gas Pagardewa - Mohamad Adli; M Nurtian Passabena; Rifky Amri Amrullah; Isa Elfianto; Haerul Jamal; Fanny Shinta Junita; Rifdah Athifah Gunawan; Allyssa Maulida Azzahra (Prospect Publishing, 2024)
The Corporate Social Responsibility (CSR) program is a strategy used by companies to have a positive impact on the community and environment around their operational areas. PT Perusahaan Gas Negara (PT PGN) as an energy company has a vision to become a leading and trusted national gas company. To improve the economic welfare of the community, PT PGN implements a CSR program which includes a rubber farmer empowerment program. Evaluation of the level of community satisfaction with this CSR program was carried out through a survey using a questionnaire developed from PermenPANRB 14/2017. Data collection was carried out on September 11, 2023, in Pagar Dewa Village, Lubai Ulu District, Muara Enim Regency, South Sumatra Province. The research results show that the level of community satisfaction with PT PGN Pagardewa's CSR program is relatively high, with a Community Satisfaction Index (IKM) value of 94.75 in the